Glacier anomaly over the western Kunlun Mountains, Northwestern Tibetan Plateau, since the 1970s - YETANG WANG; SHUGUI HOU; BAOJUAN HUAI; WENLING AN; HONGXI PANG; YAPING LIU (Journal of Glaciology, 2018)
Western Kunlun Mountain (WKM) glaciers show balanced or even slightly positive mass budgets in the early 21st century, and this is anomalous in a global context of glacier reduction. However, it is unknown whether the stability prevails at longer time scales because mass budgets have been unavailable before 2000. Here topographical maps, Shuttle Radar Topography Mission and Landsat data are used to examine the area and surface elevation changes of glaciers on the WKM since the 1970s. Heterogeneous glacier behaviors are observed not only in the changes of length and area, but also in the spatial distribution of surface elevation changes. However, on average, glacier area and elevation changes are not significant. Glaciers reduce in the area by 0.07 ± 0.1% a−1 from the 1970s to 2016. Averaged glacier mass loss is −0.06 ± 0.13 m w.e. a−1 from the 1970s to 1999. These findings show that the WKM glacier anomaly extends back at least to the 1970s.